2021
DOI: 10.11648/j.ijg.20210502.16
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 Study of EDP-305, a Novel Once-Daily Oral Farnesoid X Receptor Agonist, in Healthy Subjects and Those with Presumptive Nonalcoholic Fatty Liver Disease

Abstract: Introduction: EDP-305 is a farnesoid X Receptor (FXR) agonist that selectively activates FXR and is currently under investigation for with the treatment of nonalcoholic steatohepatitis (NASH). The primary objective was to assess the safety of EDP-305 in healthy subjects and subjects with presumptive NAFLD. Methods: In this placebo-controlled doubleblind Phase 1 study, healthy subjects (aged 20-55 years) were randomized to single or multiple oral doses of once daily EDP-305 or placebo and subjects with presumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…PD effects indicative of FXR activation have shown a more pronounced effect in patients with presumptive NAFLD and NASH when compared with healthy subjects. 25,31,[37][38][39] In this study with EDP-297, target engagement was confirmed by decreases in C4 levels and increases in FGF-19 levels during 14 days of treatment. Increases in liver enzyme levels have been observed with other FXR agonists.…”
Section: Discussionsupporting
confidence: 64%
“…PD effects indicative of FXR activation have shown a more pronounced effect in patients with presumptive NAFLD and NASH when compared with healthy subjects. 25,31,[37][38][39] In this study with EDP-297, target engagement was confirmed by decreases in C4 levels and increases in FGF-19 levels during 14 days of treatment. Increases in liver enzyme levels have been observed with other FXR agonists.…”
Section: Discussionsupporting
confidence: 64%
“…A relative bioavailability assessment indicated that EDP‐305 tablet has approximately twofold higher exposures compared to the suspension (data on file). Results from phase I studies in healthy subjects and subjects with presumptive NAFLD 4 and a phase II study in subjects with NASH 5 suggest that the optimal therapeutic dosage range for EDP‐305 is 1–2 mg (tablet) once daily. These DDI studies were conducted at clinically relevant doses, and can be applied to future studies in patients with NASH.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] In phase I studies, EDP-305 was well-tolerated in healthy subjects at single doses up to 80 mg and in subjects with or without presumed nonalcoholic fatty liver disease (NAFLD) at multiple daily doses up to 20 mg for 14 days. 4 In a 12week, phase II study that evaluated the safety, tolerability, and efficacy of EDP-305 in 132 non-cirrhotic patients with fibrotic NASH, treatment with EDP-305 reduced hepatic enzyme levels and liver fat with a tolerability profile that was consistent with other FXR agonists. 5 Results from preclinical studies indicate that EDP-305 has a low potential to inhibit cytochrome (CYP) 1A2, 2B6, 2C8, 2C9, 2C19, 2D6, and 3A4 isoenzymes or to induce CYP1A2, 2B6, and 3A4 in standard hepatic microsome studies.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations